The aura of Alif : the art of writing in Islam - Frembgen, Jurgen Wasim (Prestel, 2010)
Starting with the alifA", the first letter of the Arabic alphabet that symbolizes divine beauty and exploring the fascinating aesthetic qualities of calligraphy, the book presents the contextual and symbolic intentions of writing in religion, magic, and poetry. Writing surfaces include not only parchment, papyrus, and paper, but also ceramics, metal, stone, wood, leather, and textiles. Ranging from the early period of Islam to the 21st century, the book presents works from the art of the ruling elite to folk art and everyday aesthetics. Muslim cultures' artistic forms of expression are brought to life in this lavishly illustrated book, which includes contributions by renowned international experts in their field and explores the art of writing in Islam in all its richness and diversity. -- Product Description